(untitled) (Research, Society and Development, 2020)
Parasitic infections cause a greater number of public health problems, mostly affecting fewer children, including children and adolescents. On a limited topic on the topic addressed as one of the agents promoted for the disease, the present study aims to assess parasitic indices and knowledge about the prevention of enteroparasitosis in students of a state school located in the city of Maranhãozinho-MA. Data collection occurred through the application of questionnaires, including objective and subjective questions and also through the analysis of sample samples from students studied in the study. The data were compiled in tables and graphs with information in absolute and relative values. With an analysis of the students’ samples, it was found that 38.00% of the participants were infected with less than one species of parasite. Only protozoa were found, being: Entamoeba coli (50.00%), Endolimax nana (37.40%), Entamoeba histolytica / dispar (12.50%) and Giardia lamblia (12.50%). The results of this study indicate that the true panorama of intestinal parasitosis is known as a limited way by the population evaluated. Health education actions, such as the practice of educational activities and interactive exercises that help and facilitate the absorption of knowledge, are some of the measures that can be carried out in the school program or in order to promote an improvement in the current scenario.